Intravenous immunoglobulins in dermatology. Part 2: clinical indications and outcomes. (1st August 2018) - Forbat, E.; Ali, F. R.; Al‐Niaimi, F.
Summary: Intravenous immunoglobulin (IVIg) is a solution of human IgG, salt, sugars and solvents used to treat a multitude of diseases. Although IVIg has been known to treat many diseases safely and successfully, there are relatively few supporting randomized controlled trials. In part two of this review, we assess the clinical indications of IVIg in dermatological disorders and the outcomes of its use. Abstract : Click here for the corresponding questions to this CME article.